A multisample dissolution dynamic nuclear polarization system for serial injections in small animals. Issue 2 (22nd February 2016) - Krajewski, Marcin; Wespi, Patrick; Busch, Julia; Wissmann, Lukas; Kwiatkowski, Grzegorz; Steinhauser, Jonas; Batel, Michael; Ernst, Matthias; Kozerke, Sebastian
Abstract : Purpose: Several in vivo applications of dissolution dynamic nuclear polarization (DNP) require rapid successive injections of hyperpolarized substrates. Here we present the design and performance of a custom‐built multisample dissolution DNP setup for small animal research. Methods: The DNP setup consists of a commercial wide‐bore magnet charged to 3.35 T, a cryostat, a 94‐GHz microwave source, and a custom‐built skeleton that accommodates four identical sample sticks. Each sample stick features a dissolver locked into the skeleton port and a lifter, which permits moving the sample cup out of the liquid helium bath for dissolution. Results: The dissolution of the first sample was triggered after 2 hours of polarization buildup during single‐shot operation of the cryostat. Thereafter, a time window of 75–90 min was available to dissolve the remaining three polarized samples. The average liquid state polarization over all four sticks was measured as 18.7% ± 2.3% for [1‐13C] pyruvate 30 s after dissolution. In vivo applicability of the setup using serial injections of [1‐13C] pyruvate to study cardiac metabolism in rats revealed good reproducibility. Conclusion: The proposed four‐sample DNP insert provides reproducible liquid state polarization of [1‐13C] pyruvate and allows for rapid repeat injections in small animals. Magn Reson Med 77:904–910, 2017. © 2016 International Society for Magnetic Resonance in Medicine